Multiple Intelligences in Arabic Language Teaching: An Experimental Study in Islamic Junior High School/ Kecerdasan Majemuk dalam Pembelajaran Bahasa Arab: Studi Eksperimen di Madrasah Tsanawiyah - Dewi Nur Masitho; Saudati Alfira Rahmatillah (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2026)
This study aims to analyze the effectiveness of a differentiated instruction model based on multiple intelligences in improving Arabic reading skills (maharah al-qira’ah) of eighth-grade students at MTs Negeri 1 Sidoarjo. The study employed a quantitative approach using a quasi-experimental method with a one-group pretest–posttest design. The population consisted of 310 eighth-grade students, while the sample comprised 33 students from class VIII-B selected through purposive sampling with the criteria that the class demonstrated relatively low Arabic reading proficiency and diverse learning characteristics. The treatment involved the implementation of differentiated instruction integrated with a multiple intelligences approach through various learning activities such as the use of visual media, group discussions, language games, and reading exercises tailored to students’ intelligence potentials. The results indicate an improvement in students’ Arabic reading skills after the implementation of the model. These findings highlight the importance of adaptive instructional strategies that accommodate students’ diverse characteristics to support more inclusive and student-centered Arabic language learning.Penelitian ini bertujuan menganalisis efektivitas model pembelajaran berdiferensiasi berbasis kecerdasan majemuk dalam meningkatkan keterampilan membaca bahasa Arab (maharah al-qira’ah) siswa kelas VIII di MTs Negeri 1 Sidoarjo. Penelitian menggunakan pendekatan kuantitatif dengan metode eksperimen semu melalui desain one-group pretest–posttest. Populasi penelitian berjumlah 310 siswa kelas VIII, sedangkan sampel terdiri dari 33 siswa kelas VIII-B yang dipilih menggunakan teknik purposive sampling dengan kriteria kelas yang memiliki kemampuan membaca bahasa Arab relatif rendah serta menunjukkan keragaman karakteristik belajar. Perlakuan penelitian berupa penerapan pembelajaran berdiferensiasi yang dipadukan dengan pendekatan kecerdasan majemuk melalui berbagai aktivitas seperti penggunaan media visual, diskusi kelompok, permainan bahasa, dan latihan membaca yang disesuaikan dengan potensi kecerdasan siswa. Hasil penelitian menunjukkan adanya peningkatan kemampuan membaca bahasa Arab setelah penerapan model tersebut. Temuan ini menegaskan pentingnya strategi pembelajaran yang adaptif terhadap keberagaman karakteristik siswa untuk mendukung pembelajaran bahasa Arab yang lebih inklusif dan berpusat pada peserta didik.